Influenced of threshold fluence, absorption coefficient and thermal loading in laser paint removal mechanisms - Mohammad Khairul Azhar Abdul Razab; M.S. Jaafar; A.A. Rahman; S. Mamat; Muhamad Iqbal Ahmad; F.M. Suhaimi (Taylor & Francis Group, London, 2015)
This study aimed to investigate the influenced of FT, α and γ in laser paint removal mechanisms over three types of car coated substrates irradiated by Cynosure Cynergy Pulse Nd:YAG laser. Depth of coating removed (d) versus laser Fluence (F) graphs were plotted for each Pulse Width (PW), Repetition Rate (RR) and Beam Size (BS) considered by measuring the average of coating removal efficiency (∈). The best threshold fluence for sample A, B and C were selected from the best interception of the fitted linear graph of ∈ with their X-axis to estimate the general threshold fluence (FT) for each sample. By applying Beer-Lambert law, absorption coefficient (α) and thermal loading (γ) were also estimated. The study concludes the FT, α and γ were obtained at 42 J/cm2 , 209.80 cm−1 and 8811.76 J/cm3 for sample A, 63 J/cm2 , 68.92 cm−1 and 4341.73 J/cm3 for sample B and 14 J/cm2 , 143.23 cm−1 and 2005.21 J/cm3 for sample C respectively.